Genetic context of blaCTX–M–55 and qnrS1 genes in a foodborne Salmonella enterica serotype Saintpaul isolate from China - Li, Lili; Olsen, Rikke Heidemann; Xiao, Jian; Meng, Hecheng; Peng, Shifu; Shi, Lei (Frontiers in Microbiology, 2022)
Salmonella enterica resistant to fluoroquinolones (FQs) and extended-spectrum cephalosporins (ESCs) has been deemed a high-priority pathogen by the WHO. Salmonella enterica serovar Saintpaul (S. Saintpaul) co-resistant to ESCs and FQs and harboring corresponding resistance genes (blaCTX–M–55 and qnrS1) have been previously reported. However, they have not been reported in China. Moreover, the genetic context and transferability of ESCs and FQs resistance genes in S. Saintpaul remain obscure. This study is the first study to characterize a multidrug-resistant (MDR) S. Saintpaul isolate (16Sal016) harboring plasmid-mediated blaCTX–M–55 and qnrS1 genes recovered from weever fish in China. The whole genome short- and long-read sequencing results identified the presence of 15 acquired antibiotic resistance genes encoding resistance to nine classes of antibiotics, as well as abundant mobile genetic elements residing on a 259,529 bp IncHI2 plasmid. The blaCTX–M–55 and qnrS1 genes were located in a 12,865 bp region, IS26-orf-orf-ISKpn19-qnrS1-IS3-Tn3-orf-blaCTX–M–55-ISEc9-orf-IS26. Similar structures have been identified in various bacterial species, indicating a high transferability of blaCTX–M–55 and qnrS1 genes within this gene cluster. The plasmid was found to be transferable to Escherichia coli (E. coli) J53 by conjugation and resulted in the acquisition of multiple resistances by the transconjugants. Genome sequence comparisons by core genome multilocus sequence typing (cgMLST) based on global 2,947 S. Saintpaul isolates indicated that strain 16Sal016 was epidemiologically linked with an isolate from the United Kingdom (UK). Our findings suggest that plasmids and IS26-mediated mobile genetic elements are carriers of blaCTX–M–55 and qnrS1 genes in S. Saintpaul, and highlight their potential transmission, which needs continuous investigations.